The United States in the World Arena / An Essay in Recent History - Rostow W.W (Hodder & Stoughton, 1969)
A brilliantly perspective and penetrating assessment of America's position and prospects. Preface, Author's Introduction, A Prologue: Variations on Three Themes, The Second World War, The Truman-Stalin Duel, The Eisenhower Administration and Its Crisis, Prospects and Problems, The American Agenda, The National Interest, American Project Books and Working Papers, Index.